Saturday

January 31, 2015

January 31, 2015

Posted by **kingwendu** on Saturday, December 17, 2011 at 6:52am.

- function ( partial fraction) -
**Steve**, Saturday, December 17, 2011 at 3:35pmWell, thinking fg(x) means f(x) * g(x) I get no consistent solution. So, making

fg(x) = f(g(x)) we have

f(g) = ag^2 + bg + c

= a/(3x^2+2)^2 + b/(3x^2+2) + c

= [a + b(3x^2+2) + c(3x^2+2)^2] / (3x^2+2)^2

= 9cx^4 + (12c+3b)x^2 + (4c+2b+a)

= 18x^4 + 24x^2 + 11

That makes c=2, b=0, a=3, so f(x) = 2x^2 + 3

**Answer this Question**

**Related Questions**

partial fraction - if f(x) ax^2+bx+c , g(x) :1/3x^2+2 and fg(x)= 18x^4+24x^2+11...

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

Math - (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+...

Math - Find the Least Common multiple of the two expressions: 24x^2-96 & 18x^2+...

Math - Find the HCF of f(x) = 6x^3 + 24x^2 + 18x, g(x) = 4x^4 + 4x^3 - 24x^2

BobPursley..here it is: - Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common ...

Math - Express in partial fraction.7x^2-18x-7 divided by (x-4)(2x^2-6x+3)

Math - Express in partial fraction.7x^2-18x-7 divided by (x-4)(2x^2-6x+3)

algebra - -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for ...

Algebra (Re.: Reiny) - The fact that there was that nice symmetry to the ...